Parasitism by Clinostomum marginatum (Clinostomidae) in neotropical electric fish (Gymnotiformes) in the Brazilian Amazon - Chagas de Souza, Darlison; Nogueira, Adília; Corrêa, Lincoln Lima (Annals of parasitology, 2020)
Gymnotiformes are currently recognized as electric fish, the vast majority of which emit low power electrical discharges. Clinostomum trematodes have been the subject of numerous investigations in several host species due to the ability of metacercariae of this genus to infect the muscles, fins and internal organs of fish. The present study aimed to record, for the first time, the occurrence of parasitism by Clinostomum marginatum in Gymnotiformes from the natural environments of two tributaries of the Amazon River in the Brazilian Amazon. Two specimens of Gymnotus coropinae, ten specimens of Brachyhypopomus brevirostris, two specimens of Gymnorhamphycthys petiti and one specimen of Microsternarchus bilineatus were captured. Infection with C. marginatum was identified in the form of 12 encysted metacercariae in the epidermis, with a prevalence of 0.1%, a mean infection intensity of 12/fish and an average abundance of 1.2. This is the first record of parasitism by the C. marginatum in South American Gymnotiformes of the B. brevirostris species.